Pengaruh Flexibel Working Arrangement dan Work Life Balance terhadap Kinerja Karyawan pada PT Chahra Sidoarjo - Yuliandany, Elvina Windy; Hermawan, Haris; Umany, Septy Holisa (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The background of the phenomenon in this thesis is the phenomenon of setting flexible working hours which makes employees negligent in using working hours so that this results in high levels of absenteeism due to not being able to balance work and personal life thereby reducing a worker's performance. The aim of this research is to determine the impact of flexible work. The Impact of Work-Life Balance and Organization on Employee Performance. PT Chahra Event Sidoarjo is the subject of this investigation. Quantitative research is the type used. PT. Chahra Event Sidoarjo personnel constitute the research population. In this research, 55 respondents were sampled. The sampling method uses saturated sampling. Both primary and secondary data sources were used to obtain data for this investigation. The relevance of flexible work arrangements (2.906) and work-life balance is demonstrated by the t test finding (3.842) greater than 2.006 so that it partially influences employee performance. Regression analysis shows that flexible working arrangements (0.300) and work-life balance (0.397) improve employee performance. Work-life balance is the variable that has the most influence on employee performance, according to test findings using the t test. It is recommended that further research combine other characteristics, such as job satisfaction and organizational commitment. Keyword : Flexible Working Arrangements, Work Life Balance, Employee Performance